Pengaruh Varietas dan Waktu Penyiangan Gulma Terhadap Pertumbuhan dan Hasil Tanaman Kacang Hijau (Phaseolus Radiatus L.) - GOMES, EUSEBIO; WIJANA, GEDE; SUADA, I KETUT (Agrotrop : Journal on Agriculture Science, 2014)
The Effects of Variety and Weeding Times on Growth and Yield of Mungbean (PhaseolusRadiatus L.) The mungbean have a great potential as a food ingredient mixture of refined productsand has certain competitive advantages over other types of beans. Mungbean production in East Timoris still low and has not been able to meet the needs of the market. Therefore, weed control and selectionof good varieties of mung beans is one of the determining factors in the increased production of mungbean.The objective of the study was to determine the effect of time of weeding on the growth and yield ofseveral varieties of mungbean. The study was conducted at the Pilot Suco Hera Sub-distrito Cristo Rei,Dili-Timor Leste. It used a randomized block design with two factors. The first factor was type ofvarieties of mungbean and the second factor was the weeding time. Factor of types of varieties consistedof three, namely: VL = Local Variety, VM = Merak variety, VG = Gelatik variety, while factor ofweeding times consists of PO = No weeding, P1 = weeding at 2 and 4 weeks after planting, P2 =weeding at 3 and 5 weeks after planting, with three replications. The results showed that weeding timeaffected the outcome of drying seed dry weight per hectare. Weeding time at 2 and 4 weeks afterplanting had a better dry weight of seed i.e 1.09 g, compared to those of weeding at 3 and 5 weeksafter planting. The use of different varieties showed that Merak variety had drying seed dry weight of1.16 tons ha-1, Gelatik variety was 1.09 tons ha-1, and the local variety was 0.97 tons ha-1.
Keywords: Varieties of Mungbean; Weeding time; growth; yield